Assessing the structural behavior of reinforced concrete beams produced with macro synthetic fiber reinforced self-compacting concrete. (April 2022) - Uğur, Ahmet Emin; Ünal, Alptuğ
Highlights: PPF was more effective against shear forces without stirrups and at low stirrup ratio. Homogeneous fiber spread was achieved by incorporating PPFs within the SCC. PPF played an important role in the transition to bending behavior by preventing shear fracture. PPF changed the distribution of cracks on the beam surface, allowing the cracks to spread over the entire surface. Abstract: This study was carried out to investigate the effect of polypropylene-based structural macro synthetic fiber (PPF) reinforcement on the behavior of reinforced concrete beams produced with self-compacting concrete (SCC). For this purpose, it was aimed to spread the PPFs homogeneously in the concrete by making use of the fluid form of SCC. The variation of non-fibrous-low-medium-high PPF ratios and stirrup ratios in specimens produced with SCC are the variables of the study. In this study, the shear span/effective depth ratio (a/d) was taken as the limit value of 2.5 in terms of shear and bending, and the behavior of reinforced concrete beams at this critical value was investigated. Within the scope of the study, 16 large-scale specimens were tested under monotonic loads in a 4-point bending setup. Load-displacement, stiffness and energy consumption graphs of the tested specimens were drawn, ductility values were determined, crack distributions were examined and failure modes were determined. The graphs and the determined values were interpreted in detail. In addition, numerical models of the tested specimens were created and analyzed using a finite element program. Experimental study results were compatible with numerical analysis results and similar results were obtained. According to the results obtained, it was observed that the specimens produced with SCC and using PPF reinforcements at appropriate ratios (5 kg/m 3 and 10 kg/m 3 ) exhibited bending failure even if stirrups were not used.